Answer:
Step-by-step explanation:
Let [tex]y[/tex] be a solution vector of the homogeneous linear system [tex]Ax = 0[/tex], then, [tex]Ay = 0[/tex].
On the other hand, suppose that [tex]z[/tex] is a solution vector of the non-homogeneous linear system [tex]AX = b[/tex], that is, [tex]Az = b[/tex].
Now, considering the previous assumptions, you have:
[tex]A (y + z) = Ay + Az = 0 + b = b[/tex]
The above demonstrates that the vector [tex](y + z)[/tex] satisfies the system [tex]Ax = b[/tex]. Then [tex](y + z)[/tex] is a solution of the non-homogeneous linear system [tex]Ax = b[/tex]